Employment of doctors of veterinary medicine from 2010-2019 - Cvitković, Denis (Array, 2020)
The employment of veterinarians is an indicator of economic development and of the quality of the relationship between humans and nature. Several authors have published reports on the employment of veterinarians. This paper examines the trends in unemployment and employment of veterinarians according to the records of the Croatian Employment Service (CES) in the period from 2010 to 2019. The CES is a public institution of the Republic of Croatia established under the Labour Market Act (Official Gazette 118/18) that plays a key role in regulating supply and demand on the labour market of the Republic of Croatia. The average number of employed veterinarians was higher than the average number of veterinarians registered in the CES records. An average of 181 veterinarians were sought annually, 160 were employed and 143 were registered, indicating that demand surpassed supply. Veterinarians were recruited faster than the average person with a college degree, within 180 days, and very few were in longterm unemployment. Most were employed in the category of young people (up to 30 years of age), and most were employed without any previous work experience. More women than men were employed. Most veterinarians were employed in the City of Zagreb, which reflects the relatively low livestock production and depopulation of rural areas, as the traditionally main and safest source of employment for veterinarians. According to the National Classification of Economic Activities (NKD), veterinarians were employed in almost all groups of activities, allowing for greater employment flexibility and mobility on the labour market. According to the National Classification of Occupations (NKZ), on the other hand, most veterinarians were employed in group 2 (experts and scientists), likely since veterinary medicine is a regulated profession. This also means that several were employed under their qualification levels.